Systematic evaluation of horizontal gene transfer between eukaryotes and viruses - Irwin, NAT; Pittis, AA; Richards, TA; Keeling, PJ (Springer Nature, 2021)
Gene exchange between viruses and their hosts acts as a key facilitator of horizontal gene transfer and is hypothesized to be a major driver of evolutionary change. Our understanding of this process comes primarily from bacteria and phage co-evolution, but the mode and functional importance of gene transfers between eukaryotes and their viruses remain anecdotal. Here we systematically characterized viral–eukaryotic gene exchange across eukaryotic and viral diversity, identifying thousands of transfers and revealing their frequency, taxonomic distribution and projected functions. Eukaryote-derived viral genes, abundant in the Nucleocytoviricota, highlighted common strategies for viral host-manipulation, including metabolic reprogramming, proteolytic degradation and extracellular modification. Furthermore, viral-derived eukaryotic genes implicate genetic exchange in the early evolution and diversification of eukaryotes, particularly through viral-derived glycosyltransferases, which have impacted structures as diverse as algal cell walls, trypanosome mitochondria and animal tissues. These findings illuminate the nature of viral–eukaryotic gene exchange and its impact on the evolution of viruses and their eukaryotic hosts.